Pengembangan E-Modul Matematika Berbasis Matematika Realistik Bernilai Budaya Kediri pada Materi Perbandingan - Zenik Nurfadilah; Dewi Hamidah; Eka Resti Wulan (Institut Agama Islam Negeri Curup, 2023)
Based on the results of observations, the activeness of the Comparative Mathematics learning process in class VII E MTsN 2 Kediri City is still relatively low. This is because the teaching materials used are only printed teaching materials. The aim of study was to develop a Mathematics E-Module on Comparative Material with a Realistic Mathematics Approach in collaboration with Kediri Culture. This study uses the R&D method with the ADDIE model which consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. The research instruments used were material expert validation sheets, media experts, teacher response sheets, and student responses. The data analysis technique in this research is descriptive quantitative analysis. The experimental subjects in this study were students at MTsN 2 Kediri City. The results of this study indicate that the e-module developed is in the very good category with an average score of 94.5% from material expert validation, from media experts at 82.5%, from teacher response sheets at 100%, from group trials small by 83%, and from the large group trial by 81%.